From soil to cacao bean: Unravelling the pathways of cadmium translocation in a high Cd accumulating cultivar of Theobroma cacao L - Blommaert, Hester; Aucour, Anne-Marie; Wiggenhauser, Matthias; Moens, Claudia; Telouk, Philippe; Campillo, Sylvain; Beauchêne, Jacques; Landrot, Gautier; Testemale, Denis; Pin, Serge; Lewis, Caleb; Umaharan, Pathmanathan; et al. (Frontiers in Plant Science, 2022)
The research on strategies to reduce cadmium (Cd) accumulation in cacao beans is currently limited by a lack of understanding of the Cd transfer pathways within the cacao tree. Here, we elucidated the transfer of Cd from soil to the nib (seed) in a high Cd accumulating cacao cultivar, through Cd stable isotope fractionation, speciation, and localization. The plant Cd concentrations were 10-28 higher than the topsoil Cd concentrations and increased as placenta < nib < testa < pod husk < root < leaf < branch. The retention of Cd in the roots was low, and light Cd isotopes were retained in the roots and heavier Cd isotopes were transported to the shoots (Δ 114/110 Cd shoot-root = 0.27 ± 0.02 ‰ (weighted average ± standard deviation)). Leaf Cd isotopes were heavier than Cd in the branches (Δ 114/110 Cd IF3 leaves-branch = 0.18 ± 0.01 ‰), confirming typical trends observed in annual crops. Nibs and branches were statistically not distinguishable (Δ 114/110 Cd nib-branch = −0.08‰ ± 0.06 ‰), contrary to the leaves and nibs (Δ 114/110 Cd nib-IF3 leaves = -0.25‰ ± 0.05 ‰). These isotope fractionation patterns alluded to a more direct transfer from branches to nibs rather than from leaves to nibs. The largest fraction (57%) of total plant Cd was present in the branches where it was primarily bound to carboxyl-ligands (60-100%) and mainly localized in the phloem rays and phelloderm of the bark. Cadmium in the nibs was mainly bound to oxygen ligands (60-90%), with phytate as the most plausible ligand. The weight of evidence suggested that Cd was transferred like other nutrients from root to shoot and accumulated in the phloem rays and phelloderm of the branches to reduce the transfer to foliage. Finally, the data indicated that the main contribution of nib Cd was from the phloem tissues of the branch rather than from leaf remobilization. This study extended the limited knowledge on Cd accumulation in perennial, woody crops and revealed that the Cd pathway is markedly different than in annual crops, which has implications for mitigation strategies.